Mengembangkan Ketrampilan Berpikir Kritis Melalui Kolaborasi Model Jigsaw dengan Model Problem-Based Learning - Gustientiedina, Gustientiedina; Jalinus, NIzwardi (INVOTEK: Jurnal Inovasi Vokasional dan Teknologi, 2020)
This study aims to support Jigsaw learning and problem based learning models (PBL) in the development of students’ thinking skills. This study used an experimental design using a pretest-posttest group pre-experimental design. The collaboration model implementation was carried out at Pelita Indonesia Computer Science College, Pekanbaru involving 17 semester III students majoring in Informatics Engineering. Before and after the implementation of collaboration 2 models, students were given a test of critical thinking skills that arranged in the same composition. The research data in the form of pretest and posttest scores conducted by t-test and the calculated gain scores are supported by the SPSS 25 program. These scores indicate the difference between the pretest score and posttest score with a significance result of 0,000 <0.05. The average pretest and posttest scores were respectively called 46.06 and 70.59. Thus, the implementation of the Jigsaw collaboration model and problem-based learning (PBL) is effective for developing students’ critical thinking skills. From the findings of this study, there are obstacles that limit time in implementing the collaboration of the two models. This obstacle occurs when presenting the results of group discussions.